Pengaruh Return On Asset, Firm Size, Debt To Equity Ratio Dan Growth Terhadap Deviden Payout Ratio (Dpr) Pada Perusahaan Manufaktur Yang Tercatat Di Bursa Efek Indonesia (BEI) - Benu, Fransince; Mujino, Mujino; Hermuningsih, Sri (Journal Competency of Business, 2023)
This study was conducted to test variable impact return on aset, firm size, debt to equity ratio and growth towards deviden payout ratio.The study used the method purposive sampling of the company’s criteria for publishing financial reports that were audited each year over the 2015 to 2018 period and had the full data needed by researchers.Data obtained by the publication of the income statement 2015-2018.The samples used in this study were 15 companies from 432 manufacturing companies listed on the Indonesia Stock Exchange ( IDX). The data in this study were processed using SPSS with multiple linear regression.The hypothesis testing method uses a significance level of 5%.The results showed that return on assets has a significant effect on dividend payout ratio,firm size does not have a significant effect on dividend payout ratio,debt to equity ratio does not have a significant effect on dividend payout ratio and growth does not have a significant effect on dividend payout ratio.